Capitalismo e democracia: uma relação de impossibilidade, considerada a democracia em plenitude, especialmente vestindo o capitalismo a forma neoliberal - Arruda, Ricardo José Brito Bastos Aguiar de (2018)
It seeks to investigate the relationship between capitalism and democracy according to the Aristotelian logical categories of the modality, namely, necessity, possibility or impossibility. The method is essentially descriptive-discursive, starting with a critical treatment of what democracy is under the empirical and normative prism, approaching it from the original experience in the classical period of ancient Greece, notably in relation to the aspects of freedom and equality, and of its present formulation developed from the nineteenth century onwards and deeply interwoven with liberal thinking, without neglecting attributes such as solidarity, respect for diversity and minorities, participation and majority rule. Next, capitalism is examined, differentiating political and economic liberalism and subjecting it to Marxist criticism, especially as regards the intrinsically expansionist tendency and its possible limits, including spatial and natural resource depletion, suggesting that this is a moment of vertical deepening of this economic model, with the reversal of social gains achieved throughout the twentieth century, especially in the postwar period and until the 1970s. It is in the third chapter that the compatibility between capitalism and democracy is discussed, if the existence of democracy presupposes capitalism, or if, on the contrary, capitalism makes democracy impossible, or is it possible to coexist, but is difficult, especially at the moment in which there are some who advocate perceptible movements managed by capital to weaken democracy. It is concluded that capitalism is incompatible with the full development of democracy, and the neoliberal presentation is especially undemocratic, although reasonable experiences of coexistence between both are presented to us in time and space, even if they are engraved by deep contradictions, especially in the context of transnational democracy.